2017
DOI: 10.3389/fmicb.2017.02543
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Receptor and Cellular Ortholog of the Marek's Disease Virus (MDV) CXC Chemokine

Abstract: Marek's disease virus (MDV) is a cell associated alphaherpesvirus that causes fatal lymphoma in chickens. One factor that plays a crucial role in MDV pathogenesis is the viral CXC chemokine vIL-8 that was originally named after chicken interleukin 8 (cIL-8). However, a recent study demonstrated that vIL-8 recruits B cells and a subset of T cells but not neutrophils, suggesting that vIL-8 is not a cIL-8 orthologue. In this study, we set to identify the cellular orthologues and receptor of vIL-8 using in silico … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Based on the accepted model of the MDV life cycle, after inhalation of cell-free virus particle within contaminated dust and dander, epithelial cells are infected first, followed by phagocytes like macrophages and DCs [4]. At this time, B cells, along with T cells, are recruited to the lung by MDV-encoded viral IL-8, a functional orthologue of chemokine CXCL13L1 but distinct from chicken IL-8 [93,94], which recognizes the C-X-C chemokine receptor type 5 (CXCR5) on B and T cells and induces chemotaxis [94]. Subsequently, B cells become the primary target cell for productive MDV replication after the virus is carried to lymphoid tissues by infected macrophages and DCs.…”
Section: B Cellsmentioning
confidence: 99%
“…Based on the accepted model of the MDV life cycle, after inhalation of cell-free virus particle within contaminated dust and dander, epithelial cells are infected first, followed by phagocytes like macrophages and DCs [4]. At this time, B cells, along with T cells, are recruited to the lung by MDV-encoded viral IL-8, a functional orthologue of chemokine CXCL13L1 but distinct from chicken IL-8 [93,94], which recognizes the C-X-C chemokine receptor type 5 (CXCR5) on B and T cells and induces chemotaxis [94]. Subsequently, B cells become the primary target cell for productive MDV replication after the virus is carried to lymphoid tissues by infected macrophages and DCs.…”
Section: B Cellsmentioning
confidence: 99%
“…Chemotaxis assay were performed as described before (20). Briefly transwell plates (Sigma-Aldrich, Taufkirchen, Germany) were coated with 50 µl fibronectin (10 µg/ml) and then incubated for 1 h at 37 • and 5% CO 2 .…”
Section: Chemotaxis Assaymentioning
confidence: 99%
“…The same chemokine receptor and ligand have been shown to be key players in many other migration processes, including the mobilization of mammalian hematopoietic stem cells, lymphocytes (14)(15)(16) but also primordial germ cells (17). CXCR4 and its ligand CXCL12 are both expressed in chickens during B cell development (18)(19)(20)(21). It has been suggested that immature B cells might also migrate toward the bursa under the influence of the CXCR4/CXCL12 interaction.…”
Section: Introductionmentioning
confidence: 99%
“…MDV secretes a viral CXC chemokine that was initially termed vIL-8, but recently changed to vCXCL13 based in its biological properties [25][26][27][28]. This chemokine recruits B cells and a subset of Mononuclear phagocytes transfer the virus to lymphoid organs, such as the spleen, thymus, and bursa, where the virus lytically replicates in lymphocytes.…”
Section: Novel Insights Into the MDV Life Cyclementioning
confidence: 99%